Percutaneous drainage of abdominal fluid collections that require laparotomy or relaparotomy with ultrasound giudance - Miletić, Damir (Radiology and oncology (Ljubljana), 2001)
Background. The aim of the study was to determine efficacy and reliability of percutaneous abdominal drainage in surgical patients and to evaluate intercostal approach to drain subphrenic collections. Material and methods. Eighty-seven patients aged from 29 to 84 years (mean, 55.5 years) were percutaneously drained under the sonographic guidance due to the postoperativeor nonoperated abdominal collection that would otherwise require laparotomy. Intercostal, subcostal, lateral and anterior approach with eight to 14 French catheters were used to evacuate abdominal collection. Results. The intercostal approach was used to drain 31 (60.8% of 51 subphrenic collections. The mean duration of drainage was independent of the intercostal or subcostal drainage route, but was significantly prolonged (p<0.05, Mann-Whitney U test) for purulent collections (median, 18 days; range 7-73 days) in comparison to hematomas, bilomas and other nonpurulent collections (median, 11 and 6 days, respectively). Sonographically guided percutaneous drainage was a definitive method in 92% patients, with 9.2% minor complications. Successful rate for subphrenic collections was even greater (96%). Conclusions. Sonographically guided percutaneous drainage is the methodof choice in the treatment of abdominal collections that require laparotomy. If the puncture site is at least two intercostal spaces lower thanthe dome of diaphragm and catheter is not introduced through the pleural effusion, intercostal drainage is equally efficient and not less secure than subcostal approach.
Keywords: Abdomen; Ascitic fluid; Colonic neoplasms; Drainage; drenaža; Laparotomy; Postoperative complications; sonografija; Subphrenic abscess; tekočina; trebušna votlina; Ultrasonography; ultrasound; ultrazvok